A network based fetal ECG monitoring algorithm - Ibrahimy, Muhammad Ibn; Hasan , M. A.; Motakabber, S. M. A. (INSI Publications, 2011)
Now telemedicine is producing a great impact for health care of the patients, especially who are located in the remote nonclinical environments. This paper presents a research work that concerns to implement simple customized and portable emergency medical care information for Fetal Electro Electrocardiography (FECG) monitoring system. The research work is included both the hardware and software. The hardware part is developed for abdominal Electrocardiography (AECG) data acquisition system. Individual algorithms and customized application software are developed using Visual Basic for both the networking and Fetal Heart Rate (FHR) monitoring systems. The hardware data acquisition system acquires the mother’s AECG data by using a commercial ECG frontend microchip, called CARDIC and stores the data in a local computer terminal. The networking application program serves the purpose to transfer the AECG data to the remote computer terminal for diagnosis purpose. The AECG signal is processed into the remote computer terminal and finally extracts the FECG signal by the FHR monitoring program. The networking program is developed by a client/server approach and it can transport the AECG data file as well as online chatting facility. A specialist physician at the remote terminal can diagnose the AECG data file and can be taken an immediate action if necessary. Proposed system is used to study numbers of cases and satisfactory result is found compared with conventional systems.